ANALISIS KEARIFAN LOKAL RIMBA PUAKA SUKU TALANG MAMAK - Lika Apriani; M. Jaya Adi Putra; Zufriady Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Local wisdom is a custom that is firmly held and maintained by the local community and certain tribes. Culture entering the community can change the values that exist in the local community. The purpose of this study was to establish the local wisdom of the Rimba Puaka of the Talang Mamak tribe. The type of research used in this study are ethnographic research methods incorporated into qualitative research. Data collection methods used are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this study indicate that the local wisdom of Rimba Puaka is still maintained and preserved by the Talang tribe. Local Wisdom Rimba Puaka is a forest sacred by the community. This is apparent from the results of interviews conducted by researchers. Interviews were conducted with several informants from the indigenous Talang Mamak tribe.Key Words: Local Wisdom; Jungle Puaka, Talang Mamak Tribe Community